FREQUENCY ANALYSIS OF DELTA SCUTI VARIABLE STARS. II. - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analyses performed for photoelectric observations of two delta Scuti stars V1162 Ori and AV Cet show that these stars are multiperiodic with most significant frequencies identified as radial mode overtones and their linear combinations.